Evaluation of the primary school nutrition programme in Mogodumo area, Limpopo Province - Moabelo, Mmasesolo Francina (University of Limpopo (Turfloop Campus), 2006)
Nutrition is a basic human right as well as a prerequisite for the realization of full intellectual and physical potential. This is also stipulated in the South African Constitution and the Bill of rights. The Limpopo Province is known as one of the most poverty and drought stricken provinces in the RSA with a very high rate of unemployment. To alleviate poverty and to improve health and school attendance, the state president enhanced the Primary School Nutrition Programme on 1 September1994 in a number of targeted primary schools according to their poverty level. This study focused on the formative phase of the evaluation of the Primary School Nutrition Programme in the Mogodumo Circuit of the Capricorn District in the Limpopo province. It is a formative phase as it is an ongoing process. Mogodumo circuit is situated ± 56 km, west of Polokwane City, with 90% of the primary schools situated in the rural area. For this study, the researcher employed the probability sampling method in two stages. A simple random sampling of five schools selected was done while the stratified sample was obtained at each of those five selected schools. Through qualitative research, the qualitative data were obtained through a questionnaire, interviews and observation. The final results from the study show that though the learners’ school attendance had improved, they (learners) were eating the food because “beggars are not choosers”. The food they were receiving was of a poor quality, not delicious and not according to the tender specifications. There were no community involvement in the education of their children, unfaithful suppliers and helper mothers (volunteers), principals were forced to sign for the quality of food that was not received, passive participation of the teachers and their involvement in the decision making of the PSNP issues, a lack of facilities such as water, electricity, kitchens and fences. The helper mothers (volunteers) were complaining about the heavy job they were doing without a living wage as they only received a thankyou token of R110-00 per month. The programme was thus functioning in contradiction to rules and policies laid down for it.
Thesis (M.Dev.) --University of Limpopo, 2006
Keywords: School nutrition programmes; 371.716; Educational research -- South Africa; School children -- Food -- South Africa; Nutrition -- Evaluation